TANGGAP FISIOLOGIS TANAMAN JAGUNG DAN KACANG TANAH DALAM SISTEM TUMPANGSARI DI LAHAN BERIKLIM KERINGTHE PHYSIOLOGICAL RESPONSES OF MAIZE PEANUT - INTERCROPPING SYSTEM IN TROPICAL SEMI-ARID DRYLAND - Laode Sabaruddin; Yonny Koesmaryono; Hidayat Pawitan; H.M.H Bintoro Djoefrie (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2003)
Abstract is available in the full text (pdf format)